Association extraction for vitamin E recovery from deodorizer distillate by in situ formation of deep eutectic solvent. Issue 6 (24th December 2016) - Qin, Lei; Li, Jiangsheng; Cheng, Hongye; Chen, Lifang; Qi, Zhiwen; Yuan, Weikang
Abstract : An innovative intensified vitamin E (VE) recovery process from the methylated oil deodorizer distillates (MODDs) was proposed, where VE was in situ transferred into a deep eutectic solvent (DES) with an organic salt. To design the process, the chlorine based quaternary ammonium salts were primarily investigated, and [N4, 4, 4, 4 ]Cl was selected as an association solvent which can efficiently form DES with α‐tocopherol of the representative compound of VE. Based on the determined phase diagram of the DES freezing points, four phase regions were classified, and the effect of the [N4, 4, 4, 4 ]Cl/tocopherol ratio and temperature on the extraction performance and phase transformation was figured out. Moreover, an intensified association extraction process via in situ forming DES of α‐tocopherol with [N4, 4, 4, 4 ]Cl was designed and validated by experiments. VE products were finally obtained from both model MODD (purity of 99.63%) and practical MODDs (purity of >79.18%), which verifies the excellent extraction efficiency for the proposed recovery method. © 2016 American Institute of Chemical Engineers AIChE J, 63: 2212–2220, 2017